Supremachist Constructions of Gender in Multiplatform Fictional Narrations and Patriarchal Statism: From conceptual representation to socio-political projection (2023)
Is male ‘supremachism’ really over? The pages you are holding in your hands sow doubts on the common belief that the governance of ‘the macho’ came to its end. As the proverb confirms, ‘the old dies hard’, despite the yet-to-improve individual and institutional efforts to achieve gender equality. With the serious tone this capital issue requires, the author debunks the myth of male supremacism as a phenomenon from a past and raises awareness of the subliminal survival of the supremachist ideological apparatus. Subtlety reveals as a key factor for the survival of subliminal supremachist campaigns, which threatens a promising future of non-discrimination. Essentially, democratic citizenship must pose itself a crucial question: Are current Western societies’ concessions to feminism genuine or a cover by supremachism to survive in an ideologically volatile world?S’ha acabat realment el ‘supremacisme’ masculí? Aquestes pàgines sembren dubtes sobre l’opinió comuna que el govern d’"els mascles" ha arribat a la fi. Com confirma el proverbi, ‘the old dies hard’, malgrat els esforços individuals i institucionals per aconseguir la igualtat de gènere. L’autora desmunta el mite del supremacisme masculí com un fenomen del passat i alerta de la pervivència subliminal de l’aparell ideològic supremacista. La subtilesa es revela com un factor clau per a la supervivència de les campanyes subliminals supremacistes, que amenacen un futur prometedor de no discriminació. Atesa la importancia cabdal d’aquest tema, la ciutadania democràtica ha de plantejar-se una pregunta crucial: les actuals concessions de les societats occidentals al feminisme, són autèntiques o una tapadora del supremacisme per a sobreviure en un món ideològicament volàtil?
Keywords: Desigualtat; gènere; construcció narrativa; estatisme; conceptualització; alteritat; supremachisme